Implementasi PSAK 109 Akuntansi Zakat, Infaq dan Shadaqah di Badan Amil Zakat Nasional (BAZNAS) Pontianak - Redhea, Yaswinta Ulfa (Jurnal KIAFE, 2022)
This study aims to analyze the application of zakat accounting based on PSAK 109 at the BAZNAS Pontianak. The approach used is researcher use a qualitative method descriptive analysis. The result showed that (1) The accounting process at the BAZNAS Pontianak was not fully in accordance with general accounting theory; (2) Recognition and measurement of zakat on BAZNAS Pontianak was in accordance with PSAK 109; and (3) Presentation and disclosure on BAZNAS Pontianak was not in accordance with PSAK 109.Keywords: PSAK 109, Zakat, Infaq, BAZNAS, Financial Statement